Experimental investigations on combustion and emission characteristic of GCI engine fuelled E20 blend. Issue 1 (1st January 2020) - Ngo, Van Thanh
Abstract: In this study, an experimental investigation of a gasoline compression ignition (GCI) engine on combustion and emission fuelled gasoline—ethanol blend (E20). A diesel engine was modified and driven by an electrical motor to control the engine speed at 1500 rpm and IMEP at 4.5 bar. The aim of the given study was investigated to optimize the double-injection strategy including the injection timing of the second injection timing (SOI2 ), and the dilution ratio as the exhaust gas recirculation (EGR). The SOI2 was varied from −9 to −3 CA ATDC and dilution was simulated by using N2 addition with a maximum level on 25%. It was shown that the combustion phase can be directly controlled by both SOI2 and dilution. For the SOI2 at −9 CAD ATDC, the combustion starts just after the beginning of the second injection and is delayed as a function of the dilution rate. Otherwise, the exhaust gas recirculation level was investigated to study the combustion and emissions characteristic with three cases of second injection timing while the first injection timing, fuel proportion and the intake pressure were kept constant: −35 CAD ATDC, 30%/70%, and 1 bar, respectively. The results have shown that NOx level decreased as a function of dilution for all SOI2 with the smallest NOx level at—3CAD ATDC. However, CO and HC emission increased while increasing the dilution ratio. It is clear for SOI2 is set at −3 CAD but between −6 and −9 CAD, the level of CO and HC emissions is really in the same order of magnitude.